Efficiency of energy dissipators in the seismic response of buildings - Saldaña Vasquez, Keyvin Yuliño (2022)
This paper aims to study the efficiency of energy dissipators, both fluid viscous and hysteretic, to improve the seismic responses of buildings. To quantify the ability of energy dissipators to reduce seismic responses, a series of time history analyzes were carried out on simplified models of buildings. Said simplified models consist of masses and springs with linear and elastic behavior whose properties are obtained from a shear beam model, joined by link elements with non-linear behavior to simulate energy dissipators. The main study parameters that were considered are the fundamental period of the structure without seismic control devices and the objective reduction factor. Likewise, a procedure is proposed for the dimensioning of the hysteretic dampers that will be incorporated into a building. On the other hand, the main building of the Lima airport was used as a case study, for which two alternatives are proposed, each one with a different type of energy dissipator, but both designed to have similar performance. Finally, the reductions obtained by both the simplified models and three-dimensional models are compared. It is concluded that the simplified models allow a fast and acceptable prediction of the levels of reduction of the seismic response in buildings that incorporate energy dissipators.